Cross-Sectional Study: The Impact of Parental Knowledge on Fine Motor Skills in Early Childhood Education in Peguyangan - Sundaram, Ida Ayu Agung Tri Ananda; Saraswati, Ni Luh Putu Gita Karunia; Saraswati, Ni Luh Putu Gita Karunia (Majalah Ilmiah Fisioterapi Indonesia; Vol 13 No 2 (2025): Majalah Ilmiah Fisioterapi Indonesia, 2025)
Introduction : The development of fine motor skills in early childhood is significantly influenced by environmental stimulation, particularly from parents and early childhood education (PAUD). Insufficient stimulation may result in developmental delays or lasting disorders. Parents need adequate knowledge to provide age-appropriate stimulation. In addition, early childhood educators can facilitate development through structured learning activities and media. Methods : This study used a cross-sectional observational design with purposive sampling involving 51 participants. Parental knowledge of play stimulation was assessed using a structured questionnaire completed by the parents. Children’s fine motor skills were evaluated using the Denver Developmental Screening Test (DDST). Results : Analysis using Spearman’s rho demonstrated a significant relationship between parental knowledge of play stimulation and children’s fine motor development (p = 0.029; r = 0.306), indicating a low to moderate positive correlation. Furthermore, early childhood education was significantly associated with fine motor skills (p = 0.015; r = 0.339), suggesting that structured educational environments play a role in supporting motor development. Conclusion : The study found a significant relationship between parental knowledge of play stimulation and early childhood education with fine motor skill development in Peguyangan Village, Denpasar. These results highlight the importance of enhancing parental understanding of child development and the value of quality early education programs. Educated parents can provide effective play-based stimulation, while PAUD institutions can deliver structured developmental support. These findings support the integration of parental education and PAUD programs into community health center initiatives aimed at improving early childhood development. Keywords : knowledge, parents, stimulation, early childhood education, fine motor skills, children